PEREKAYASAAN SISTEM DETEKSI VIRUS FLU BURUNG DALAM TUBUH PASIEN - Budi Santoso; Romadhon Romadhon; Sukandar Sukandar; Istofa Istofa (Jurnal Perangkat Nuklir, 2010)
ENGINEERING OF AVIAN INFLUENZA VIRUS DETECTION SYSTEM IN A PA TlENT'S BODY. The avian influenza virus detection equipment in a patient's body has been made. Currently, detection of avian influenza virus carried out by expensive laboratory equipments, so only certain hospitals can perform this detection. This developing equipment is expected to be cheaper than existing equipment and the diagnosis can be known immediately. The sensing device is made using the principle of nuclear radiation detection. Radiation comes from a drunk labelled tamiflu (oseltamivir) which is drunk to the patient. Tamiflu is a drug to catch H5N1 viruses in a patient's body. A labelled tamiflu is tamiflu which is labelled by 1-131 radioisotopes. The presence of virus in the body is proportional to the amount of radiation captured by the detector. The equipment is composed of a Geiger-Mueller (GM) pancake detector type, a signal processor, a counter, and a data processor (computer). The GM detector converts the radiation that comes into electrical signals. Electrical signal is then converted into TTL level pulses by the signal processor. Pulse counting results are processed by data processor. The total count is proportional to the amount of virus captured by labelled tamiflu. The measurement threshold can be set by medical officer through software. At a certain threshold can be inferred identified patients infected with avian influenza virus. If the measurement below the threshold means that the patient is still within safe limits. This equipment is expected to create avian influenza virus detection system that cheaply and quickly so that more and more hospitals are using to detect the avian influenza virus.  PEREKAYASAAN SISTEM DETEKSI VIRUS FLU BURUNG DALAM TUBUH PASIEN. Telah dibuat perangkat pendeteksi virus flu burung dalam tubuh pasien. Saat ini pendeteksian virus flu burung dilakukan dengan peralatan laboratorium yang mahal, sehingga hanya rumah sakit tertentu saja yang dapat melaksanakan pendeteksian ini. Alat yang dikembangkan ini diharapkan lebih murah dari peralatan yang sudah ada dan hasil diagnosisnya dapat diketahui dengan segera. Alat pendeteksi yang dibuat menggunakan prinsip pendeteksian radias